1997
DOI: 10.1103/physrevlett.79.4798
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of Phonon Friction for a Xenon Film on a Silver (111) Surface

Abstract: Molecular dynamic simulations for a Xe film sliding on an Ag(111) substrate are performed from the submonolayer through the bilayer regime, which, when compared to both friction and surface resistivity measurements, demonstrate that the friction in this system is dominated by phonon excitations. Slip times are found both by direct calculation of the decay of the center-of-mass velocity, as well as from the decay of the velocity correlation function. Agreement of the slip times from the two methods supports the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
115
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 16 publications
12
115
0
Order By: Relevance
“…8 Despite the fact that they used similar models and similar simulation techniques to calculate the phononic contribution to friction, they got quite different results. Persson and Nitzan 3 found that the phononic friction was not significant in comparison with the electronic contribution, while Tomassone et al 4 found the opposite. On the other hand Liebsch et al 5 concluded that both contributions are important, but that the phononic friction strongly depends on the substrate corrugation amplitude.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…8 Despite the fact that they used similar models and similar simulation techniques to calculate the phononic contribution to friction, they got quite different results. Persson and Nitzan 3 found that the phononic friction was not significant in comparison with the electronic contribution, while Tomassone et al 4 found the opposite. On the other hand Liebsch et al 5 concluded that both contributions are important, but that the phononic friction strongly depends on the substrate corrugation amplitude.…”
Section: Introductionmentioning
confidence: 90%
“…[2][3][4][5] Subsequently, a huge body of new and fascinating experiments on nanoscale friction has seen the light during the last 15 years. However, the theoretical interpretation of nanoscopic sliding experiments has evidenced some degree of disagreement, mainly related to incompatible results between different simulations, [3][4][5] in spite of the fact that they were performed for the same system with similar models and techniques. With the aim of finding some plausible explanation for these discrepancies we set out to study the relation between the topology and sliding friction coefficient .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In past decades, considerable research has been focused on investigating the friction behaviors at the microor nano-scales based on theory and simulations. The concept of friction has been extended in a number of associated areas, such as using surface roughness [3,4], phonon and electron excitation [5][6][7], and dislocation interaction theories [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…2 Microscopic experiments on friction, 3 and subsequent theory and simulation were started only in the last 15 years. [4][5][6][7] Of the work that remains to be done to achieve a coherent picture of this complex phenomenon, an important aspect concerns nonlinear sliding friction. In his seminal paper, 8 Persson presented numerical simulations in the nonlinear regime of an adsorbate sliding over a periodic potential.…”
Section: Introductionmentioning
confidence: 99%